The influence of the work environment and job satisfaction on work productivity at the Pompengan Jeneberang River Basin Center - Fazira, Erra; Ruma, Zainal; Kurniawan, Agung Widhi; Sahabuddin, Romansyah; Syahrul, Khaidir (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
The purpose of this study was to determine the effect of work environment and job satisfaction on employee work productivity at the Pompengan Jeneberang River Basin Center. This study used a quantitative associative approach. The population was 514 employees and the sample used in this study was 52 respondents at the Pompengan Jeneberang River Basin Center using the Accidental Sampling Technique. Data collection techniques used were observation and questionnaires. The data analysis technique used was multiple linear regression using Statistical Product and Service Solution (SPSS) software. The results of the study significantly showed that work environment and job satisfaction partially had a significant positive effect on work productivity. Furthermore, the work environment and job satisfaction simultaneously have a significant influence on work productivity.